Subjective learning gain from a simulation-based health management course: a mixed methods study - Gu, Ren-Ping; Zhao, Fang; Bai, Jie; Sun, Shan-Shan; Zhu, Ai-Yong (Frontiers in Public Health, 2024)
Objectives Simulations are increasingly being offered as part of the educational experience of healthcare students. We used a Health Management Scenario Simulation system to create a course. This study aimed to evaluate learning gains before and after the course. Methods Based on the learning strategies of framing, simulation, and debriefing, the Health Management Scenario Simulation course lasted 4 weeks and was conducted online. Learning gain was assessed using a comparative self-assessment questionnaire administered electronically at the beginning and end of the course. We organized focus group interviews and collected quantitative data after students completed the simulations and the questionnaire. These data were subjected to descriptive statistical analysis and thematic grouping using frequency counting. Results There were 195 health management students enrolled in the course. In total, 265 anonymously completed questionnaires were received, 141 (72.31%) on the pre-simulation and 124 (63.59%) on the post-simulation. All questionnaire item gain values were positive, except the item “I can identify common health risk factors,” which showed no change. The skills domain showed the highest learning gain, ranging from 16 to 22%. Six students participated in the focus-group study. The main themes that emerged from students’ reflections were learner-centeredness, competencies, and career development. Conclusion Students acquired health management skills through the simulation, which contributed to the development of basic attitudes and skills in their professional careers. Students’ comments highlighted the value of practicing health management skills in a simulated environment.